Real Options Approach to Financial Valuation of Brands (2019)
Intangible assets are an important component of the market value of a company, particularly in brands which represent the competitive advantage of the company; however, both Accounting and Finance face a great challenge when trying to value them. The methods which have been proposed by the literature appear to be subjective, limited, and based on some theoretical errors. Their use is mainly circumscribed to the management of intangibles. This paper proposes a methodology for the financial valuation of brands based on the application of a compound real option model to a patent valuation, acknowledging the similarities in their construction. Later, an application to an insurance company is presented.